ANALISIS MANAJEMEN DAN STRATEGI USAHA SAMBAL PECEL (Studi Kasus Kelompok Usaha Sambal Pecel Dasa Wisma Delima dan Larasati Madiun) - Putri Handayani, Wahyu Prabawati; Vinsensius Widdy Tri Prasetyo, Vinsensius Widdy Tri Prasetyo (Widya Warta, 2021)
This research discussed comprehensively the startup strategy of the sambal pecel group of Dasa Wisma Delima, Mojorejo, and Larasati, Taman Madiun City. The business strategy was analyzed by using the External Factor Evaluation (EFE) matrix, the Internal Factor Evaluation (IFE) matrix, the Strength-Weaknesses-Opportunities-Threats (SWOT) matrix, and the Internal-External (IE) matrix. Three indicators of on-time delivery, production planning based on-demand analysis, and business infrastructure showed good performance results. Meanwhile, other indicators that needed attention were the accuracy of production cost estimates, the accuracy of revenue planning, the accuracy of technology availability, and the accuracy of predicting the average demand. Based on the SWOT analysis, we had formulated 4 (four) business strategies consisted of business development strategies by utilizing funding facilities and cooperation between shops and universities (SO strategy), increasing production capacity through business funding facilities from the government (WO strategy), product differentiation based on experience and training to develop a business (ST strategy), and brand mindedness and production efficiency by taking into account price fluctuations and quality of raw materials (WT strategy). Therefore, the recommended strategy from the IE matrix was a Hold and Maintain strategy that was achieved by applying market penetration and product development strategies.